Ifugao males, learning and teaching for the improvement of maternal and child health status in the Philippines: an evaluation of a program - Dulnuan Marcelyn M; Takahashi Miyako; Iwasa Hajime; Kadomoto Noriko; Kai Ichiro (BMC, 2011)
Abstract Background Improving Maternal and Child Health (MCH) is a prioritized global agenda in achieving the United Nations Millennium Development Goal 5. In this challenge, involving males has been an important agenda, and a program with such intent was conducted in Alfonso Lista, Ifugao, of the Philippines. The objectives of this study were: (1) to evaluate the effectiveness in knowledge, attitude, and practice before and after a MCH session; (2) to evaluate the session's effectiveness in relation to socio-demographic characteristics; and (3) to examine if males who have learned about MCH topics can teach another group of males. Methods A male community representative who received a lecture from the health office staff was assigned to teach a group of community males [Group 1, N = 140] in 5 sessions, using educational materials. 10 male volunteers from Group 1 then taught a different group of males [Group 2, N = 105] in their own barangays (villages). To evaluate its effectiveness, a self-administered questionnaire survey pertaining knowledge, attitude and practice regarding MCH was conducted at three different time points: before the session (Time 1, T1), after the session (Time 2, T2), and 3 months following the session (Time 3, T3). A repeated measures analysis of variance was conducted to test for changes over time and its interaction effect between specific socio-demographic variables. Results In Group 1, there was a significant positive increase in knowledge score over time at T1-T2 and T1-T3 (p < 0.001). For attitude, the score increased only at T1-T2 (p = 0.027). The effectiveness in knowledge and attitude did not vary by socio-demographic characteristics. As for practice, majority of the participants reported that they had talked about MCH topics in their community and assisted a pregnant woman in some ways. A comparison between Group 1 and Group 2 revealed that Group 2 had similar effectiveness as Group 1 in knowledge improvement immediately after the session (p < 0.001), but no such improvement in the attitude score. Conclusion Although the change in attitude needs further assessment, this strategy of continuous learning and teaching of MCH topics within community males is shown to improve knowledge and has a potential to uplift the MCH status, including the reduction of maternal deaths, in Alfonso Lista, Ifugao, Philippines.